2021
DOI: 10.3389/fimmu.2021.617671
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Long Pentraxin 3 Exerts a Protective Role in a Murine Model of Pulmonary Fibrosis

Abstract: Pulmonary fibrosis is a progressive scarring disease of the lungs, characterized by inflammation, fibroblast activation, and deposition of extracellular matrix. The long pentraxin 3 (PTX3) is a member of the pentraxin family with non-redundant functions in innate immune responses, tissue repair, and haemostasis. The role played in the lungs by PTX3 during the fibrotic process has not been elucidated. In this study, the impact of PTX3 expression on lung fibrosis was assessed in an intratracheal bleomycin (BLM)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
3
10
0
Order By: Relevance
“…In the same model, Ptx3 -/mice showed reduced survival (Figure 1C) and accentuated weight loss (Figure 1C). Corroborating the results by Maccarinelli et al (29), lungs from Ptx3 -/mice showed hemorrhagic areas (day-14)(Figure 1C) and increased fibrosis, as assessed by total collagen content (day-22) (Figure 1D). In Ptx3 -/mice lung homogenates (Figure 1E), fibrosis was not associated with differences in IL-4, IL-10, IL-6, and CCL2, thus indicating the independence of PTX3 in the regulation of inflammation (1, 2, 31), while we found increased TGF-b1 in Ptx3 -/mice (Figure 1E)(day-14).…”
Section: Ptx3 and Lung Fibrosis: Lessons From Experimental Models Of Pulmonary Fibrosissupporting
confidence: 86%
See 4 more Smart Citations
“…In the same model, Ptx3 -/mice showed reduced survival (Figure 1C) and accentuated weight loss (Figure 1C). Corroborating the results by Maccarinelli et al (29), lungs from Ptx3 -/mice showed hemorrhagic areas (day-14)(Figure 1C) and increased fibrosis, as assessed by total collagen content (day-22) (Figure 1D). In Ptx3 -/mice lung homogenates (Figure 1E), fibrosis was not associated with differences in IL-4, IL-10, IL-6, and CCL2, thus indicating the independence of PTX3 in the regulation of inflammation (1, 2, 31), while we found increased TGF-b1 in Ptx3 -/mice (Figure 1E)(day-14).…”
Section: Ptx3 and Lung Fibrosis: Lessons From Experimental Models Of Pulmonary Fibrosissupporting
confidence: 86%
“…Data reported by Maccarinelli et al (29) and our results suggest that IPF may be related to a low expression of PTX3 in lung tissue. Therefore, we could consider restoring PTX3 levels exogenously (as summarized in Figure 1G) as a possible therapeutic approach for IPF.…”
Section: Therapeutic Opportunities Of Ptx3 In the Context Of Ipf: What Mechanisms Would Be Involved?supporting
confidence: 77%
See 3 more Smart Citations